2001
DOI: 10.1016/s0165-0327(00)00191-9
|View full text |Cite
|
Sign up to set email alerts
|

Can personality traits predict increases in manic and depressive symptoms?

Abstract: Background-There has been limited research investigating personality traits as predictors of manic and depressive symptoms in bipolar individuals. The present study investigated the relation between personality traits and the course of bipolar disorder. The purpose of this study was to identify specific personality traits that predict the course of manic and depressive symptoms experienced by bipolar individuals.Methods-The sample consisted of 39 participants with bipolar I disorder assessed by the Structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
4
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 33 publications
6
98
4
10
Order By: Relevance
“…Other findings suggest that overly positive views of the self (Lam, Wright, & Sham, 2005), Behavioral Approach System sensitivity (Meyer, Johnson, & Winters, 2001), beliefs about the importance of goals (Alloy et al, 2009;Francis-Raniere, Alloy, & Abramson, 2006), and goal engagement (Lozano & Johnson, 2001) can predict increases in mania. Evidence across these studies suggests an important role for cognitive and personality variables related to goal dysregulation as predictors of the course of manic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings suggest that overly positive views of the self (Lam, Wright, & Sham, 2005), Behavioral Approach System sensitivity (Meyer, Johnson, & Winters, 2001), beliefs about the importance of goals (Alloy et al, 2009;Francis-Raniere, Alloy, & Abramson, 2006), and goal engagement (Lozano & Johnson, 2001) can predict increases in mania. Evidence across these studies suggests an important role for cognitive and personality variables related to goal dysregulation as predictors of the course of manic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…38 A prospective study in BD I patients showed that a high Achievement-striving facet score predicted increases in manic symptoms. 39 This facet is regarded as a propensity of BD I rather than BD II patients. Competence measures the tendency to believe in self efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in confidence are tied to setting higher goals on tasks. Intriguingly, goal engagement has been found to predict increases in manic symptoms over a several month period (Lozano & Johnson, 2001). A range of research is congruent with the idea that dysregulation in goal pursuit, perhaps related to poor control of reward pathways in the brain, is an important contributor to manic symptoms (Johnson, 2005).…”
Section: Conceptual Integrationmentioning
confidence: 93%